Diagnostic value of circulating bone turnover markers osteocalcin, cathepsin K, and osteoprotegerin for osteoporosis in middle-aged and elderly postmenopausal women - Lei Zhang; Jiaxiang Cheng; Hang Su; Zhaoxia Wang; Weiyi Dai (Archives of Medical Science)
Introduction Material and methods Results Conclusions